Pengaruh Bimbingan Dan Konseling Islam Terhadap Hasil Belajar Siswa Di Kelas VIII Mts Al-Fathimiyah - Meilisa, Shania Azhari; H. Mansyur, H. Masykur; Abidin, Jaenal (Peneliti.net, 2023)
The aims of this study were to find out: Islamic guidance and counseling at MTs Al-Fathimiyah, student learning outcomes at MTs Al-Fathimiyah, the effect of Islamic guidance and counseling on student learning outcomes in class VIII MTs Al-Fathimiyah. The approach used in this research is descriptive quantitative. The type of research used is correlational. Data collection techniques used by researchers are observation, interviews, questionnaires (questionnaire) and documentation. The data analysis technique used by researchers is the pearson product moment correlation and the coefficient of determination. The results of the study: Islamic guidance and counseling services at MTs Al-Fathimiyah, namely 46 or at intervals of 41-60 are sufficient categories, the learning outcomes of class VIII MTs Al-Fathimiyah are in good category with the highest average score being 94 and the lowest average being 80, Islamic guidance and counseling services have an influence on learning outcomes because the rcount value is greater than the rtable, namely 0.610 > 0.374 at 5% significance by calculating R square = r2 = 0.372. These results indicate that there is a significant influence of Islamic guidance and counseling services on student learning outcomes of 37.2% and the remaining 62.8% is influenced by other variables.